Taxation, Data and Destination : An Analysis of Destination-Based Taxation from the Perspective of Tax Principles and Data Protection Regulation. - Sinnig, Julia. (IBFD Doctoral Series, 2022)
The book analyzes two destination-based corporate tax models, their application to different types of digitalized business models, and their compliance with tax and data protection law frameworks.